Does preoperative patient’s estimated acceptable pain affect the satisfaction with postoperative pain management? - Shigematsu-Locatelli, Marie; Kawano, Takashi; Kitamura, Sonoe; Nishigaki, Atsushi; Yamanaka, Daiki; Aoyama, Bun; Tateiwa, Hiroki; Yokoyama, Masataka (JA clinical reports, 2017)
Background Patient satisfaction with postoperative pain management is an important quality indicator in patient health care, but its determinants are poorly understood. Here, we examined the contribution of the discrepancy between an individual’s estimated acceptable and actual postoperative pain scores to the overall satisfaction with pain treatment. Findings A total of 93 surgical patients were included in this study. Preoperatively, the subjects were asked to rate their estimated acceptable postoperative pain using a numerical rating scale (NRS). One day after the surgery, the patients were again asked to give NRS ratings of the overall actual pain intensity they had experienced, as well as their satisfaction with the provided pain treatment. The median estimated acceptable and actual NRS values for postoperative pain were 4.0 (3.0–5.0) and 4.0 (2.0–5.0), respectively. Although there was no correlation between the degree of patient satisfaction and preoperative estimated acceptable pain intensity, there was a significant negative correlation between the degree of patient satisfaction and postoperative actual pain intensity. When the preoperative estimated acceptable NRS value was compared with the postoperative actual value for each individual, postoperative NRS was greater in 34 cases (36.6%), less in 43 cases (46.2%), and equal in 16 cases (17.2%). The degree of patient satisfaction was not significantly correlated with the magnitude of difference between preoperative estimated acceptable NRS and postoperative actual NRS. Conclusions Our findings suggest that inquiring about the estimated acceptable pain before surgery may not help anesthesiologists to understand the patient’s goal of pain management for improving patient satisfaction.